การพัฒนาแบบวัดคุณลักษณะอันพึงประสงค์ของนักเรียนมัธยมศึกษาตอนต้น ตามหลักสูตรแกนกลางการศึกษาขั้นพื้นฐาน พุทธศักราช 2551 - สุขใจ ชนนิกานต์; แกมเกตุ วรรณี (An Online Journal of Education, 2018)
Psychological assessment is the assessment of abstract traits. The quality information is investigated from the valid measure. Psychological measure have mainly long that effect to the response rate. Like the desirable characteristic scale interested that isn’t used based on the objective of the scale in order to the number of the items. The objective of this research were: 1) to develop a desirable characteristic scale for lower secondary school student in long form and short form. 2) to evaluate and compare the psychometric properties of both. Samples were 711 grade 8 secondary school student in Lopburi. The measure was a desirable characteristic scale that was called long form. The method to select an item to short form is decision on the value of corrected item-total correlation, and factor loading investigated from the result of confirmatory factor analysis (CFA). The research findings were as follows: 1. The results after developing are long form situational test, 95 items and short form situational test, 56 items. They were used to evaluate 8 desirable characteristics following Kohlberg’s moral development theory. Both scale were a decision of reliability range from 0.524 to 0.828. The construct validity that observed from the measurement model fit quite well with the empirical data set. Both scale were a contruct validity in a good ranged (chi-square/df range from 0.21 – 2.03, GFI range from 0.98 - 1.00, AGFI range from 0.97 – 1.00, RMR range from 0.008 – 0.036). The comparison between short form and long form reliability is higher than short form and construct validity in short form model is more related to the empirical data than long form model. According to the result of both scale those could be a valid scale to evaluate the desirable characteristics of student. In context of use it can reduce the time to response 20 minutes at least. But if the details of interested trait was evaluated, the long form could be choose.